Pengaruh Marketing Mix Dan Service Quality Terhadap Kepuasan Nasabah Melalui Brand Equity Pada PT Bank Bukopin Tbk Periode 2016 - Ratnawati; Maksum, Choiril; Jasin, Moch (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
The purpose of this research is to determine the influence of Marketing Mix and Service Quality on Customer Satisfaction through Brand Equity at PT Bank Bukopin Tbk, Cikarang branch. The sampling technique used is purposive sampling, with a total sample of 265 respondents. The research analysis technique employs Structural Equation Modeling (SEM). The research results show that Marketing Mix and Service Quality have a significant effect on Customer Satisfaction. This study also indicates that Marketing Mix and Service Quality significantly influence Customer Satisfaction through Brand Equity. The study proves that the higher the quality of service, the greater the level of customer satisfaction. Based on the analysis, companies can develop more effective marketing strategies, leading to improved service quality, which ultimately enhances customer satisfaction.